PENGARUH MODEL PENDIDIKAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN DATAR - Indah Karuniati Laia; Regina Sipayung; Ribka Kairani Sembiring; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article describes the effect of a realistic mathematical education model on students’ learning outcomes on flat-building learning materials. The method of research used was the Quasi-Experimental research method. The research population involved 60 students of SD Negeri 101900 Lubuk Pakam in the academic year 2020/2021. The population of class IV A as the experimental class was 30 students and class IV B as the control class was 30 students. Students' mathematical learning outcomes in the even semester of class IV A showed that in the experimental class using the provision of realistic mathematics education models before conducting the pre-test, the average score was 55.80 in the less category level and after providing the treatment of realistic mathematical education model, the post-test was 81.29 in very good category level. Students' mathematical learning outcomes in the even semester for class IV B showed that in the control class using the conventional method before being treated, the average pre-test was 52.70 in the less category level and after being treated with conventional methods, the post-test average was 74.62 in good category level. Based on t-test analysis, it was obtained tcount 1.745 > ttable 1.671 with a significance level of 0.05 or 5%. Hence, the researcher concluded that Ho was rejected and Ha was accepted. Ha was stated accepted because the average score of learning outcomes by applying a realistic mathematical education model had an effect on students who were studied by applying the conventional method.